COVID-19 and child development: educational material for family members - Mirela de Oliveira Figueiredo; Ana Luiza Alegretti; Lilian Magalhães (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to describe methodological procedures, theoretical foundation, activities and guidelines that compose an educational material designed for family members with a focus on the development of babies and children from 0 to 5 years old during the pandemic period. Methods: methodological research was applied to the preparation and validation of the educational material. The elaboration involved a literature review, graphic material creation and a validation by experts. Results: the literature review provided materials and background on child development principles and forms of stimulation through the realization of child occupations. The stage of validation by specialists provided a greater degree of reliability regarding the potential to stimulate activities and adequacy of the written elements of the material. Conclusions: the methods employed made it possible to develop, evaluate and improve the educational material, ensuring greater quality to guide and assist families in the daily stimulation of their children and in the management of occupational disruption. The material can also be useful for education and health professionals, support undergraduate education and/or university extension activities that focus on child development.